Implicit measures of environmental attitudes: a comparative study - Martha Patricia Sánchez; Arturo de la Garza González; María Isolde Hedlefs (International Journal of Psychological Research, 2016)
The present investigation aims to inquire about the capacity of three implicit instruments to measure the attitude toward natural and urban environments. One hundred and three students from a Mexican public university participated in the investigation. The implicit instruments used were the affective priming technique, the implicit association test, and the affect misattribution procedure. Further, an explicit scale was used for comparison. The results showed that all instruments converge in the same way; the nature images were viewed as more pleasant compared to the city images. Also, most results indicated good effect size values, observed power, and reliability, with the exception of the affective priming technique, which established low values. In addition, all instruments indicated weak correlations between each other. The results were discussed in terms of the capacity of the instruments to measure environmental attitudes, and also possible theoretical and methodological implications.